2020
DOI: 10.1183/23120541.00254-2019
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of latent tuberculosis among refugee children in Malaysia

Abstract: IntroductionTuberculosis remains one of the top 10 major causes of global mortality, imposing social–economic and medical challenges in Malaysia. Refugees sheltered in Malaysia are a high-risk population but basic health checks upon their arrival, including tuberculosis screening, are not practised. This study aimed to identify the prevalence and risk factors of tuberculosis and latent tuberculosis infection (LTBI) among refugee children in Malaysia.MethodsA cross-sectional study was performed in three refugee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Myanmar is ranked as one of the top 30 countries with the highest levels of tuberculosis infections (Kanabus, 2021;WHO, 2020d). Several studies have shown high prevalences of latent infections in Myanmar and Rohingya refugees (Chaves et al, 2009;Jasmine et al, 2018;Wong & Lee, 2020), whereas levels of active infections were mainly low (Chaves et al, 2009;Jasmine et al, 2018).…”
Section: Infections Spread By Close Contactmentioning
confidence: 99%
“…Myanmar is ranked as one of the top 30 countries with the highest levels of tuberculosis infections (Kanabus, 2021;WHO, 2020d). Several studies have shown high prevalences of latent infections in Myanmar and Rohingya refugees (Chaves et al, 2009;Jasmine et al, 2018;Wong & Lee, 2020), whereas levels of active infections were mainly low (Chaves et al, 2009;Jasmine et al, 2018).…”
Section: Infections Spread By Close Contactmentioning
confidence: 99%
“…Several countries have provided their citizens with a quarantine allowance, as these individuals should not miss out on any economic employment opportunities while being quarantine to protect the health of the general public [3] . Many individuals with TB currently suffer from catastrophic costs due to the need to seek and receive healthcare (range USD 120-490), which significantly reduces the TB treatment success rates [4,5] . Indeed, studies have suggested that free TB treatment and care is currently insufficient to prevent households from incurring catastrophic total cost due to TB.…”
Section: Providing a Social Safety Networkmentioning
confidence: 99%
“…According to the data, the trend of new TB incidence cases was rising and slightly decrease in 2020. Meanwhile, World Health Organization stated that the annual number of TB mortality dropped by 45% nationwide between 2000 and 2019 [1]. However, the 2030 Sustainable Development Goals (SDGs) target of 90% mortality reduction from the 2015 baseline and extinction of the TB endemic has yet to be met.…”
Section: Introductionmentioning
confidence: 99%